PERANCANGAN ABSENSI PEGAWAI ENGINEERING COFFEE BERBASIS IOT (INTERNET OF THINGS) - Alfarandi Rozul Dwi Arlovi; Firman Firman; Sahiruddin Sahiruddin (Universitas Citra Bangsa, 2025)
This study aims to design an Internet of Things (IoT)-based attendance system to enhance efficiency, accuracy, and employee discipline at Engineering Coffee. The research employed the Research and Development (R&D) method with the Waterfall model, encompassing the stages of needs analysis, system design, implementation, and testing. Data were collected through observation, interviews, literature review, documentation, and user surveys. The attendance system is equipped with ESP32Cam devices integrated with a mobile application and Google Spreadsheet for real-time recording. The testing results showed a 100% validation rate for all system components, including IP/WiFi connectivity, data processing, and application interface. Evaluation through user questionnaires revealed an average user satisfaction score of 83.75%, categorized as “Highly Feasible.” The system successfully addresses the limitations of manual attendance methods, which were previously inaccurate and inefficient, providing a practical solution that can be applied to various work environments.